(untitled) - Seagrave, Sterling (New York, 1999)
In The Yamato Dynasty, Sterling Seagrave, who divulged the secrets of Mao Tse-tung and the ruthlessness of Chiang Kai-shek in the New York Times bestseller The Soong Dynasty, and his wife and longtime collaborator, Peggy, present the controversial, never-before-told history of the world’s longest-reigning dynasty–the Japanese imperial family–from its nineteenth-century origins through today. In the first collective biography of both the men and women of the Yamato Dynasty, the Seagraves take a controversial, comprehensive look at a family history that crosses two world wars, the bombing of Hiroshima and Nagasaki, the American occupation of Japan, and Japan’s subsequent phoenix-like rise from the ashes of the Second World War. The Yamato Dynasty tells the story of the powerful men who have stood behind the screen–the shoguns and financiers controlling the throne from the shadows–taking readers behind the walls of privilege and tradition and revealing, in uncompromising detail, the true nature of a dynasty shrouded in myth and legend.
Keywords: Emperors,Meiji; Biography,Emperor of japan; 1852-1912; Japan